Pengaruh Penggunaan Alat Peraga Murah Dalam Pembelajaran Sistem Tata Surya Terhadap Hasil Belajar Siswa - Tihazanah Tihazanah (Jurnal Dedikasi Pendidikan, 2019)
In fact, IPA is very necessary in daily life. Therefore science is taught since elementary school age children. But in this case many schools still have National Based School Examination (USBN) scores in low science subjects. No exception is the 57 State Elementary School of Banda Aceh which experienced the same thing. This may be due to many factors, one of which is the use of teaching aids in learning that are used by the teacher in the process of teaching and learning activities (KBM). In connection with this the problem in this study is the influence of the use of inexpensive teaching aids in the learning of the solar system on the learning outcomes of class VI students of SD Negeri 57 Kota Banda Aceh. The aim of this Classroom Action Research (PTK) is to use elementary school as the teacher. Elementary School Science (SD) Conceptually as a provision to teach elementary school science materials. Population in the research of 57 elementary school students in Banda Aceh City. Determination of the sample in the study was class VI students of SD Negeri 57 Kota Banda Aceh, amounting to 33 people consisting of 17 male students and 16 female students. Based on the results of Classroom Action Research (CAR) it can be concluded that students of class VI SD Negeri 57 Kota Banda Aceh. Learning outcomes increased by using inexpensive teaching aids on the learning of the solar system towards class VI students of SD 57 in Banda Aceh 2018/2019.